2019
DOI: 10.15405/epsbs.2019.12.04.191
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual And Moral Values Of Youth As A Basis Of Social Orientation

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-Noncommercial 4.0 Unported License, permitting all non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…A similar survey at the cross-national level can measure the critical characteristics of this developmental process. Thus, it was found that 64% of international youth is categorized as going through the development of spiritual and moral resilience devoid of a solid commitment to overt religious and spiritual practices [24].…”
Section: Resultsmentioning
confidence: 99%
“…A similar survey at the cross-national level can measure the critical characteristics of this developmental process. Thus, it was found that 64% of international youth is categorized as going through the development of spiritual and moral resilience devoid of a solid commitment to overt religious and spiritual practices [24].…”
Section: Resultsmentioning
confidence: 99%